A pairwise and network meta‐analysis comparing the efficacy and safety of progestogens in threatened abortion. Issue 3 (18th May 2021) - Zhao, Hongqiong; He, Wei; Yang, Zhu
Abstract: Background: Progesterone is widely used to prevent threatened miscarriage. Objective: To determine the efficacy and safety of progestogens in the treatment of threatened miscarriage. Search strategy: PubMed, Cochrane Library, EMBASE, CNKI, CBM, and WanFang databases were searched for randomized controlled trials (RCTs) published from the date of inception of the database to August 2020. The search terms included "abortion, threatened, " "progesterone, " and "progestogens." Selection criteria: A network meta‐analysis was conducted of all the RCTs on threatened abortion so far to compare the efficacy and safety of different progestogens in the treatment of threatened abortion. Data collection and analysis: Odds ratios for dichotomous data with 95% confidence intervals were calculated and the data were pooled using a random‐effects model. The surface under the cumulative ranking area (SUCRA) was calculated for efficacy and safety with different interventions. Main results: A total of 59 RCTs with 10 424 participants were included. Oral dydrogesterone (DYD) had the lowest risk of miscarriage (SUCRA 100.0%), followed by vaginal progesterone (SUCRA 67.9%). Oral micronized progesterone had the highest risk of miscarriage (SUCRA 15.7%). Conclusion: Oral DYD is effective in the treatment of threatened miscarriage. The results of the present study can help patients make informed decisions about treatment options for threatened miscarriage. Abstract : The present meta‐analysis showed that the risk of miscarriage was lowest with the administration of oral dydrogesterone in the treatment of threatened abortion.